Ethical Principles for Physician Rating Sites - Strech, Daniel (JMIR Publications, 2011)
During the last 5 years, an ethical debate has emerged, often in public media, about the potential positive and negative effects of physician rating sites and whether physician rating sites created by insurance companies or government agencies are ethical in their current states. Due to the lack of direct evidence of physician rating sites' effects on physicians' performance, patient outcomes, or the public's trust in health care, most contributions refer to normative arguments, hypothetical effects, or indirect evidence. This paper aims, first, to structure the ethical debate about the basic concept of physician rating sites: allowing patients to rate, comment, and discuss physicians' performance, online and visible to everyone. Thus, it provides a more thorough and transparent starting point for further discussion and decision making on physician rating sites: what should physicians and health policy decision makers take into account when discussing the basic concept of physician rating sites and its possible implications on the physician-patient relationship? Second, it discusses where and how the preexisting evidence from the partly related field of public reporting of physician performance can serve as an indicator for specific needs of evaluative research in the field of physician rating sites. This paper defines the ethical principles of patient welfare, patient autonomy, physician welfare, and social justice in the context of physician rating sites. It also outlines basic conditions for a fair decision-making process concerning the implementation and regulation of physician rating sites, namely, transparency, justification, participation, minimization of conflicts of interest, and openness for revision. Besides other issues described in this paper, one trade-off presents a special challenge and will play an important role when deciding about more- or less-restrictive physician rating sites regulations: the potential psychological and financial harms for physicians that can result from physician rating sites need to be contained without limiting the potential benefits for patients with respect to health, health literacy, and equity.